Determinant Attitude and Employee Recruitment: Analysis Psikotest, Assessment, Behavioral Event Interview and Experience (Study Literarture) - Candra Susanto, Primadi; Henokh Parmenas, Naik; Firdiansyah Suryawan, Ryan; Apriyani, Irna (Greenation Publisher & Yayasan Global Research National, 2023)
The purpose of this research is to find out what factors can influence the employee recruitment process, This article aims to review and synthesize a literature review related to attitudes, employee recruitment, psychological tests, assessments, and behavioural event interviews and to see the research results of the variables to be reviewed and whether there is an influence between one variable and another. This study uses a literature review by looking for references related to the variables of several international articles. This study provides an overview of the articles obtained by describing the influence between variables. The results of the study show that several variables have an influence on the evidence of exposure in a matrix. The employee recruitment study in this literature summary article explicitly focuses on supporting variables that can accelerate employee recruitment efficiently, namely attitudes, psychological tests, assessments, and behavioural event interviews.